In a study of a population cohort in South Africa, HIV patients on antiretrovirals had nearly full recovery of employment - Bor, Jacob; Bärnighausen, Till (Health affairs, 2012)
Antiretroviral therapy for HIV may have important economic benefits for patients and their households. We quantified the impact of HIV treatment on employment status among HIV patients in rural South Africa who were enrolled in a public-sector HIV treatment program supported by the President’s Emergency Plan for AIDS Relief. We linked clinical data from more than 2,000 patients in the treatment program with ten years of longitudinal socioeconomic data from a complete community-based population cohort of more than 30,000 adults residing in the clinical catchment area. We estimated the employment effects of HIV treatment in fixed-effects regressions. Four years after the initiation of antiretroviral therapy, employment among HIV patients had recovered to about 90 percent of baseline rates observed in the same patients three to five years before they started treatment. Many patients initiated treatment early enough that they were able to avoid any loss of employment due to HIV. These results represent the first estimates of employment recovery among HIV patients in a general population, relative to the employment levels that these patients had prior to job-threatening HIV illness and the decision to seek care. There are large economic benefits to HIV treatment. For some patients, further gains could be obtained from initiating antiretroviral therapy earlier, prior to HIV-related job loss.